Avaliação da qualidade de vida associada a reabilitação com implantes dentários - Bastos, Lívia Martins Cardoso (2023)
The general objective of this study was to analyze the quality of life related to treatments with implant-supported prostheses in patients treated at postgraduate schools in Vitória and Vila Velha in the state of Espírito Santo, from November 2021 to March 2023. Initially, the impact on the quality of life of 319 patients in need of implant prostheses was evaluated and the possible associations between sociodemographic variables, use of removable prostheses, reason for seeking dental care and number of lost teeth. A questionnaire was used to define the sociodemographic and socioeconomic profile and with data on the number and location of missing teeth, use of prostheses and reason for seeking dental care. Data on patient treatment were collected from patient records and the Oral Health Impact Profile (OHIP-14) instrument was used to measure quality of life. To verify the associations between the independent variables and the dimensions assessed by the OHIP-14 instrument, the Fischer Exact Test was used and the significance level adopted was 5%. To assess the strength of the association between the independent variables and the OHIP-14 dimensions, the odds ratio (OR) was calculated and the confidence interval (CI) used was 95%. To analyze the effect of the combined dimensions, the Mantel-Haenszel test was used. The second stage of the study evaluated the quality of life of 160 patients before and after rehabilitation with prostheses. This is a prospective, uncontrolled, “before and after” longitudinal intervention study. Data collection was carried out by reapplication of the OHIP-14 via telephone 30 to 60 days after rehabilitation. Comparison of quality of life parameters before and after rehabilitation with implant-supported prostheses was carried out using the non-parametric Wilcoxon test. The predilection for impact was associated with female individuals, with low education, belonging to classes C and D/E, using removable dentures, who sought urgent care and who lost all their teeth. The number of individuals with an impact on quality of life before the proposed treatment was 216 (67.7%), and this number significantly reduced after implant treatment to 6 (3.8%).